Digital data and tools for managing agriculture: focusing on earth observation data and climate change - Ghosh, Surajit; Mallick, A.; Dawn, A.; De Sarkar, K.; Chowdhury, A.; Kour, S.; Ghosh, A.; Holmatov, Bunyod (International Water Management Institute (IWMI). CGIAR Initiative on Low-Emission Food Systems; CGIAR Initiative on Resilient Cities., 2023)
The report presents the prime aims, objectives, discussions and insights from the “Training Workshop on Digital Data and Tools for Managing Agriculture: Focusing on Earth Observation Data and Climate Change” organized at IIIT Bhubaneshwar from 21st to 23rd December 2023. The workshop was attended by 81 participants and jointly conducted by IIIT Bhubaneshwar, IWMI, and IEEE GRSS Kolkata Chapter. The primary objective of the workshop was to equip participants with practical skills and knowledge to utilize digital data and tools, especially Earth observation data, for effective agricultural management in the context of climate change and make evidence-based decisions to confront challenges in the food system, urban water pollution, GHG emissions & nexus. The programme encompassed the challenges posed by population growth, climate change and urbanization on the water, food and energy nexus, and the need to address the complexities to achieve sustainable development and mitigate environmental impacts is necessary. Through various sessions, the workshop highlighted concerns about GHG emissions and their mitigation by transitioning to renewable energy, carbon capture and storage, water hyacinth mapping in urban and peri-urban wetlands, Artificial Intelligence/Machine Learning (AI/ML) applications for rice mapping, flood damage assessment, maternal, infant and young children nutrition deficit under extreme weather conditions, agricultural data collection tools and sustainable agriculture practices. The CGIAR’s Mitigate+: Low-Emission Food Systems Initiative focuses on reducing emissions from the food systems by developing robust science, data, and evidence (among other activities). Another initiative by CGIAR on Resilient Cities generates evidence, technologies, and capacities that help improve urban food systems and secure equitable job and business opportunities, healthy diets for all, human and environmental health, and a reduced carbon footprint. Both initiatives provided resources to support the training workshop to empower students, researchers, scientists, academicians, decision-makers, and policymakers with cutting-edge knowledge and tools to integrate digital data into agricultural management practices. Participants learned about the latest advancements in Earth observation technologies, big data analytics, and digital tools that can help predict and make robust, evidence-based decisions as they confront challenges in the food system, urban water pollution, strategies to reduce GHG emissions, and tackling the nexus challenges. Thus, the workshop was envisioned as a catalyst to empower the agricultural community with digital tools and data, fostering resilience and productivity in the face of climate change. The criticality of Earth Observation (EO) data and digital tools in informing agricultural management decisions was rigorously examined and elucidated through a comprehensive program comprising six keynote addresses, nine scholarly lectures and six practical demonstrations, all facilitated by esteemed national (including IIT Guwahati, IIWM, Assam University, OSDMA, SAADRI, and SPARC) and international institutions (such as IWMI, World Bank, and DLR). A pre-event catch up with the participants was held on the first day session as a social ice-breaking session. The discourse was further enriched by an expert panel discussion on the ‘Role of Digital Tools in Mitigating Climate Change Effects on Agriculture’, an intensive brainstorming session entitled ‘Data Science and Sustainability Challenge’ and a showcase of research presentation by the participants. These engagements highlighted the practical and innovative usages of EO data for managing agriculture in the context of climatic challenges and emphasized how such strategic applications contribute towards attaining the SDGs. Of the 82 participants, 63% are male, and 37% are female. Among the attendees, 52% were at the graduate and post-graduate level, while 26% of the participants were research scholars from various Indian institutions. Of the other participants, 22% were faculty and professionals. This diversity of participants demonstrates the programme’s appeal to different professionals and researchers. The participants come from multiple institutions, including renowned universities and research centres across India like IIT Roorkee, BIT Mesra, ISI Kolkata, Techno Main Salt Lake, IIT Kharagpur, IIT Mandi, Fakir Mohan University, KIIT, and many more. This institutional diversity indicates the programme’s broader reach and appeal among academic and research organizations. These analytics provide valuable insights into the participants’ gender distribution, designations, education levels, and institutional affiliations. The inclusivity and diversity, reflected in gender representation and institutional affiliations, created a dynamic and comprehensive learning community. The diverse curriculum gave them valuable knowledge and skills to solve real-life challenges associated with major natural disasters.